Development of a sensor-based site-specific N topdressing algorithm for a typical leafy vegetable - Ji, Rongting; Shi, Weiming; Wang, Yuan; Zhang, Hailin; Min, Ju (Frontiers in Plant Science, 2022)
Precise and site-specific nitrogen (N) fertilizer management of vegetable is essential to improving N use efficiency considering temporal and spatial fertility variations among fields, while the current N fertilizer recommendation methods are proved to be time and labor consuming. To establish a site-specific N topdressing algorithm for bok choy (Brassica rapa subsp. chinensis), using a hand-held GreenSeeker canopy sensor, we conducted field experiments in the years 2014, 2017 and 2020, respectively. Two planting densities, viz; high (123,000 plants ha-1) in Year I, and low (57,000 plants ha-1) in Year II, whereas, combined densities in Year III, were used, respectively, to evaluate the effect of five N application rates (0, 45, 109, 157, 205 kg N ha-1). A robust relationship was observed between the sensor-based normalized difference vegetation index (NDVI), the ratio vegetation index (RVI), and the yield potential without topdressing (YP0) at rosette stage, and 81–84% of the variability at high density and 76–79% of that at low density could be explained. By combining the densities and years, R2 value increased to 0.90. Additionally, the rosette stage was identified as the earliest stage for reliably predicting the response index at harvest (RIHarvest), based on the response index derived from NDVI (RINDVI) and RVI (RIRVI), with R2 values of 0.59–0.67 at high density and 0.53–0.65 at low density. When using the combined results, the RIRVI performed 6.12% better than the RINDVI, and 52% of the variability could be explained. This study demonstrates the good potential of establishing a sensor-based N topdressing algorithm for bok choy, which could contribute to the sustainable development of vegetable production.